Negative Emotional States In Pregnant Women: Prevalence and Risk Factors - Yulistanti, Yeni; Sugiarto, Angga; Suyanta, Suyanta (Poltekkes Kemenkes Semarang, 2025)
Background: Negative emotional states among pregnant women is an issue that should not be ignored due to its widespread impact on the health of mothers and babies, which can last for the long term. In addition to affecting physical conditions. This study aims to describe negative emotional states in pregnant women and its risk factors.Methods: The research method used is descriptive analysis. The study population consists of all pregnant women in Magelang City, totaling 540 individuals, with a purposive sample of 214 individuals. Respondents were asked to complete a questionnaire containing data on respondent characteristics and the Depression Anxiety Stress Scale (DASS). The collected data will then be analyzed using frequency distribution tables and logistic regression to determine the influencing risk factors.Results: Prevalence negative emotional states : most experiencing mild depression (71%), most experiencing moderate anxiety (68%), with the majority experiencing moderate stress (57%), and total negative emotional states(experiencing at least one): 67,8%. Negative emotional states was higher in those aged < 20 years or > 35 years (p = 0.019), those with low education (p = 0.041), those with low family support (p < 0.001), and those with a pregnancy related illness (p = 0.024). The logistic regression results showed that the dominant risk factor was low family support (OR = 3.9; 95% CI: 1.9–7.8), followed by a pregnancy related illness (OR = 2.5; 95% CI: 1.2–5.2).Conclusion: Negative emotional statescan occur in pregnant women, especially those who are too young or too old, unemployed, have little support from their husbands, and have a history of obstetric complications. Health workers are expected to help pregnant women minimize negative emotional states .